Troubling Vice: Stigma & Subjectivity in Shakespeare's Ambitious Villains - Simonson, Thomas (Wake Forest University, 2019)
Opening with the figure of Richard III, who alludes to the stage Vice of the morality plays preceding later Elizabethan and Jacobean drama, I trace Shakespeare’s engagement with the Vice figure across two plays featuring the most infamous of his ambitious villains, Titus Andonronicus’s Aaron and Othello’s Iago, who present mirrored images of patriarchal power structures. My project troubles the traditional hermeneutics of the Vice in relation to villainy by paying careful attention to Aaron and Iago’s delegitimization through the context of Judith Butler’s Gender Trouble, which emphasizes the prediscursive ontologies that patriarchal institutions inscribe upon the individual. In doing so, I do not separate either villain from their respective play’s robust evocations of the Vice; on the contrary, I celebrate these dramaturgic and historical threads of influence in order to explore the ways in which Shakespeare’s works build on and expand the potential encapsulated in the swaggering Vice figure. I begin with a chapter briefly covering the history of the morality play before moving to an analysis of the Vice’s ascendancy and endurance beyond the confines of the homiletic genre of his origin. His linguistic agency I use as a hermeneutic key in reading anew Aaron and Iago, who insistently evoke and yet distance themselves from the Vices in their transgressive soliloquys and speeches. In this regard, my analysis posits that the Shakespearean villain reimagines the Vice as a distinctly human villain, as motivated by discernible ambitions as they are indicted for inappropriate excesses of familiar sinful desires. Accordingly, I trouble essentialized readings of their villainy in asserting that both figures rebel against social constructions they find confining, as though the Vice of the moralities at last has been granted the stage to usurp the subjectivity – and not merely the significance – of a protagonist. In making this claim, however, I qualify my recuperation of villainy throughout by examining the ways in which both villains fail to present meaningful alternatives to the systems against which they rebel. This becomes most notably apparent by positioning their careers of revenge against the fates of the women in each play, a perspective calling into question their ultimate success in posing challenges to patriarchy’s function of assigning, then confirming, prediscursive vice or Otherness.
Keywords: Aaron; Iago; Morality; Shakespeare; Vice; Villain